Dualitas Digital: Mengungkap Fenomena “Finsta” dan Strategi Komunikasi Gen Z pada Second Account di Media Instagram - Vidara Nanda; Situ Asih; Walyono Walyono (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study examines the phenomenon of using multiple Instagram accounts (first account and second account) among Generation Z students, especially members of the Buddhist Student Association of Sebelas Maret University Surakarta (IKMAB UNS). Using an observational approach and in-depth interviews, this study analyzes the differences in user communication behavior on the two accounts, including types of content, use of features, interaction patterns, language styles, and time management. A qualitative research method with a case study approach was applied to uncover the complexity of this phenomenon. The results showed a clear dichotomy: the first account is a formal and structured self-presentation space with low posting frequency but high visual quality, while the second account is a place for more authentic, spontaneous self-expression, with more intense and personalized interactions within a limited community. Significant differences were also found in language style, where the first account used formal and structured language while the second account used informal language with mixed codes. This phenomenon reflects Generation Z's adaptive strategy in managing digital identity according to the communication context and audience expectations. This research contributes to the understanding of digital communication psychology and the dynamics of Generation Z's self-presentation in the contemporary social media era.